Extreme growth plasticity in the early branching sauropodomorph Massospondylus carinatus. (12th May 2021) - Chapelle, Kimberley E. J.; Botha, Jennifer; Choiniere, Jonah N.
Abstract : There is growing evidence of developmental plasticity in early branching dinosaurs and their outgroups. This is reflected in disparate patterns of morphological and histological change during ontogeny. In fossils, only the osteohistological assessment of annual lines of arrested growth (LAGs) can reveal the pace of skeletal growth. Some later branching non-bird dinosaur species appear to have followed an asymptotic growth pattern, with declining growth rates at increasing ontogenetic ages. By contrast, the early branching sauropodomorph Plateosaurus trossingensis appears to have had plastic growth, suggesting that this was the plesiomorphic condition for dinosaurs. The South African sauropodomorph Massospondylus carinatus is an ideal taxon in which to test this because it is known from a comprehensive ontogenetic series, it has recently been stratigraphically and taxonomically revised, and it lived at a time of ecosystem upheaval following the end-Triassic extinction. Here, we report on the results of a femoral osteohistological study of M. carinatus comprising 20 individuals ranging from embryo to skeletally mature. We find major variability in the spacing of the LAGs and infer disparate body masses for M. carinatus individuals at given ontogenetic ages, contradicting previous studies. These findings are consistent with a high degree of growth plasticity in M. carinatus .